SANTO PAULUS é«˜ä¸äºŒå¹´çº§ç†ç§‘Açå¦ç”Ÿçš„æ±‰è¯å››ä¸ªå£°è°ƒæŽŒæ¡æƒ…å†µåˆ†æž - Febriyanti, Fifi; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTone is a very important part of Chinese teaching. There are four tones in Mandarin Chinese. When students read new words, they often mispronounce their tones, and their meanings will change. In order to understand the mastery and difficulties of the four tones of Chinese by the students of the second grade science class A in Santo Paulus Senior High School, this paper uses the test method to test the students to understand their mastery and analyze the four tone difficulties of Chinese. Test results show that some of the tones they have mastered well, but some of the tones they have not mastered very well. When analyzing the difficulties, the author finds that the most problematic time for students is when they read